Delayed Relief of Hemifacial Spasm After Microvascular Decompression. Issue 2 (March 2015) - Xia, Lei; Zhong, Jun; Zhu, Jin; Dou, Ning-Ning; Liu, Ming-Xing; Li, Shi-Ting
<x xml:space="preserve">Abstract</x> Abstract Microvascular decompression (MVD) has been accepted worldwide as a reasonable treatment for hemifacial spasm (HFS); however, resolution of the HFS is often gradual. To conclude the delayed relief rate of the MVD for the treatment of HFS, we conducted a systematic review. Using the keywords delayed relief, hemifacial spasm, or microvascular decompression, articles published in English-language journals and indexed in PubMed between June 1, 1994 and June 1, 2014 on the treatment of HFS with emphasis on delayed relief were considered for this study. Twelve articles with 2727 patients with HFS were finally enrolled in this review. Among all the patients, the ratio of male versus female was 1:2.7, and left versus right was 1:1.6. The average age at surgery was 52.5 years (49.1–55.9 y), with HFS symptom duration of 68.4 months (38.4–98.4 mo) before the surgery. The average follow-up duration was 49 months (6.4–121.6 mo). After examining all the patients, we obtained a mean postoperative success rate of 85.1% (76.5%–93.5%), but the success rate after the MVD immediately is only 71.8% (59.5%–84%). The mean rate of delayed relief was 25.4% (18.8%–37.1%). Approximately 13.1% (5.9%–19.7%) of the patients with symptom recurrence resorted to repeated MVD during the follow-up period. Accordingly, MVD is the most effective treatment for patients with HFS, but some of the patients may experienced delayed relief, which could be avoided if a thorough decompression of the facial nerve root had been obtained.